'Harnessing the Falls': Early South African Electrification and the Victoria Falls and Transvaal Power Company, 1906 – 1948 (Historia, 2025)
The Victoria Falls and Transvaal Power Company (VFP) was the largest generator of electricity in South Africa between 1906 and 1948. This made the VFP an extremely important driving force in the country’s economy, especially as the Rand’s mines began to rely on increasing electrical consumption as part of their mechanisation. In turn, it was this economic importance that brought the VFP into conflict with other groups that were attempting to establish their own electricity generation and distribution grids, especially so with the Rand’s municipal bodies. After the enactment of the Electricity Act of 1922, the VFP was faced with further opposition in the form of the Electricity Supply Commission (hereafter referred to by its contemporary name, Eskom). While the relationships between the VFP, Eskom, and the Rand’s municipalities has been examined in the existing body of published literature, the focus of these prior analyses has largely been centred on Marxist frameworks. Instead, this article intends to examine these relationships in terms of the complex relationships between the VFP, municipal governments, local government, and their electricity consumers.
Keywords: Victoria Falls and Transvaal Power Company (VFP); Eskom; South African Electrification